2020
DOI: 10.3389/fninf.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

Automated Hierarchy Evaluation System of Large Vessel Occlusion in Acute Ischemia Stroke

Abstract: Background: The detection of large vessel occlusion (LVO) plays a critical role in the diagnosis and treatment of acute ischemic stroke (AIS). Identifying LVO in the pre-hospital setting or early stage of hospitalization would increase the patients' chance of receiving appropriate reperfusion therapy and thereby improve neurological recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…They found that the ANN had a higher predictive value than the conventional scales (AUROC, ANN 0.823, conventional scales 0.740–0.796) 12 . In addition, prediction algorithms for LVOs using machine learning were documented by You et al, whose study was not a prehospital study but a hospital study 13 . Their study included 300 adult stroke patients (LVO n = 130) with 24 variables and compared the predictive values of XGBoost, logistic regression, random forest, and SVM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the ANN had a higher predictive value than the conventional scales (AUROC, ANN 0.823, conventional scales 0.740–0.796) 12 . In addition, prediction algorithms for LVOs using machine learning were documented by You et al, whose study was not a prehospital study but a hospital study 13 . Their study included 300 adult stroke patients (LVO n = 130) with 24 variables and compared the predictive values of XGBoost, logistic regression, random forest, and SVM.…”
Section: Discussionmentioning
confidence: 99%
“…Their study included 300 adult stroke patients (LVO n = 130) with 24 variables and compared the predictive values of XGBoost, logistic regression, random forest, and SVM. They found that XGBoost had the highest predictive value for LVOs (AUROC 0.809) 13 . In agreement with these findings, we also found that XGBoost had a higher predictive value for strokes compared to logistic regression, random forest, and SVM.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the ANN had a higher predictive value than the conventional scales (AUROC, ANN 0.823, conventional scales 0.740-0.796) 12 . In addition, prediction algorithms for LVOs using machine learning were documented by You et al, whose study was not a prehospital study but a hospital study 13 .…”
Section: Prediction Of Stroke Subcategoriesmentioning
confidence: 99%
“…Their study included 300 adult stroke patients (LVO n = 130) with 24 variables and compared the predictive values of XGBoost, logistic regression, random forest, and SVM. They found that XGBoost had the highest predictive value for LVOs (AUROC 0.809) 13 . In agreement with these ndings, we also found that XGBoost had a higher predictive value for strokes compared to logistic regression, random forest, and SVM.…”
Section: Prediction Of Stroke Subcategoriesmentioning
confidence: 99%
“…Automatic segmentation of cerebral vessels is required to perform automatic analysis of CoW variation. However, it is still challenging to segment cerebral arteries automatically due to the inhomogeneous intensity, complex topological shapes, vessel abnormality, and other complex features [ 14 , 15 ]. Conventional methods segment vessels are based on low-level features with low accuracy and efficiency [ 16 ].…”
Section: Introductionmentioning
confidence: 99%